ABSOLUTIST SOVEREIGNTY AND NATIONAL SOVEREIGNTY: THE ORIGINS OF THE NATION-STATE - Гайко, О. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The process of  state  formation of  the modern  type  (nation-states), which represents  the gradual transformation of the absolutist sovereignty to national sovereignty. It is focusing on the fact that the process  of  centralization  of  state  power  took  place  against  the  background  of  democratization  of state power in the transition from the absolutist sovereignty to national sovereignty.